Inventtory Of Randang Meat Recipes as Traditional Food in Baso District, Agam Regency - Rahmi, Sri; Elida, Elida (Universitas Negeri Padang, 2022)
The background of this research is that there is no inventory of beef rendang recipes in Baso District, Agam Regency. This study aims to take an inventory of meat rendang recipes in Baso District, Agam Regency which includes ingredients, spices, equipment and processing processes.The type of research used is qualitative. The location of this research was carried out in Baso District, Agam Regency. The source of research data is Bundo Kanduang and the community who are experts in making randang. Data collection techniques by conducting observations, interviews, and documentation. Data analysis in the field which includes data reduction, data presentation, conclusion drawing and verification.The results showed that the number of recipes for beef rendang in Baso District, Agam Regency, from 6 Nagari namely Nagari Koto Tinggi, Nagari Simaraso, Nagari Tabek Panjang, Nagari Koto Baru, Nagari Salo, and Nagari Padang Tarok there were 12 different recipes in each region. The ingredients and seasonings used are beef inner thighs, coconut milk from old coconut and half old coconut, darek red chilies, shallots, garlic, ginger, galangal, lemongrass, turmeric leaves, bay leaves and lime leaves. The tools used are basin, filter, patchwork, sanduak, stale cauldron and piriang samba. The processing process is coconut milk cooked with spices that have been mashed along with the leaves until the oil rises, then add the meat and cook until it turns blackish brown.